A review of some key climate change legislations and policies: lessons for Singapore's construction industry. (9th August 2010) - Gunawansa, A.; Kua, H.W.
There is overwhelming scientific consensus that the climate is changing due to primarily human-induced activities. Emission of greenhouse gases from the energy and construction sectors is one of the main human induced causes. Most legislative and policy initiatives by countries to deal with climate change will have a significant impact on the energy and construction sectors. In proposing the appropriate sustainability lessons for Singapore's construction industry, this paper briefly examines the international framework for dealing with climate change and the key legislative and policy initiatives in the USA and Australia, two of the largest GHG emitters in the world. This paper argues that the relevant mechanism introduced in all three countries is insufficient to deal with the impacts of climate change, as their main focus is on mitigation. The most rigorous mitigation efforts currently might not be able to prevent climate changes in the near future; hence, adaptation to climate change should become an integral part of the planning process, especially in the construction sector.